Design of distance lectures in mathematics education with the utilization of the integration of Zoom and YouTube application. (October 2020) - Subhi, M A; Nurjanah, N; Kosasih, U; Rahman, S A
Abstract: Something that is considered new must meet difficulties in its implementation. Including distance lectures. The cause can come from various factors. This research development aims to produce distance lecture design by utilizing the integration of the Zoom and YouTube applications on students of the Mathematics Education Department in a private university in Bandung. The development model uses an adaptation of the Plomp development model by carrying out two phases, namely the preliminary investigation phase and the design phase. From the results of the initial research, it can be concluded that: the development of distance lecture design is very essential, design of distance lectures include: roles in lectures (lecturer, host, and student), supporting applications (Zoom, YouTube, and OBS Studio), and interaction design that connects roles in lecturer with supporting applications, and the utilization of the Zoom and YouTube application integration has the potential to be more effective and efficient.